2020
DOI: 10.1186/s12985-020-01351-9
|View full text |Cite
|
Sign up to set email alerts
|

The molecular evolutionary characteristics of new isolated H9N2 AIV from East China and the function of vimentin on virus replication in MDCK cells

Abstract: Background: The low pathogenic H9N2 AIV caused the serious impact on the poultry industry and public safety. Our purpose was to investigate the molecular evolutionary characteristics of the new isolated H9N2 virus and investigate the intracellular target protein of H9N2 AIV replication in sensitive cells. Methods: AIV A/chicken/Shandong/LY1/2017 (H9N2) was isolated from the cloaca of the healthy chicken in Shandong, and the full-length eight gene segments of this isolated H9N2 AIV were amplified by RT-PCR and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Furthermore, the presence of surface VIM/vi-VIM is not restricted to infection with hepadnaviruses, as other viruses, such as human severe acute respiratory syndrome-related coronavirus (SARS-CoV), Japanese encephalitis virus (JEV), and enterovirus 71 (EV-A71), also induce this filamentous protein at least in vitro [ 23 , 63 , 64 , 65 ]. Surface VIM/vi-VIM is further used by SARS-CoV, JEV, EV-A71, porcine reproductive and respiratory syndrome virus, dengue virus, H9N2 subtype avian influenza virus, Chandipura virus, and cowpea mosaic virus as a receptor or at least as a co-receptor for cell attachment and entry by endocytosis, and in many studies viral infection can be reduced or even inhibited in vitro by using antibodies against VIM presented at the cell surface [ 62 , 64 , 66 , 67 , 68 , 69 , 70 , 71 ]. Although the exact mechanism of surface VIM/vi-VIM induction needs to be elucidated, infection with rather diverse viruses apparently changes the conformation of intracellular VIM thereby allowing its presentation on the cell surface.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the presence of surface VIM/vi-VIM is not restricted to infection with hepadnaviruses, as other viruses, such as human severe acute respiratory syndrome-related coronavirus (SARS-CoV), Japanese encephalitis virus (JEV), and enterovirus 71 (EV-A71), also induce this filamentous protein at least in vitro [ 23 , 63 , 64 , 65 ]. Surface VIM/vi-VIM is further used by SARS-CoV, JEV, EV-A71, porcine reproductive and respiratory syndrome virus, dengue virus, H9N2 subtype avian influenza virus, Chandipura virus, and cowpea mosaic virus as a receptor or at least as a co-receptor for cell attachment and entry by endocytosis, and in many studies viral infection can be reduced or even inhibited in vitro by using antibodies against VIM presented at the cell surface [ 62 , 64 , 66 , 67 , 68 , 69 , 70 , 71 ]. Although the exact mechanism of surface VIM/vi-VIM induction needs to be elucidated, infection with rather diverse viruses apparently changes the conformation of intracellular VIM thereby allowing its presentation on the cell surface.…”
Section: Discussionmentioning
confidence: 99%
“…BP5 was synthesized by GenScript Biotechnology Co., Ltd (Nanjing, China), and the purity determined by HPLC and mass spectrometry was 98.8%. Avian influenza virus strain A / chicken/Shandong/Ly1/2017(H9N2) was stored in our laboratory [20]. Virus was harvested from the allantoic fluid of 9-day chicken embryos, and the hemagglutination titer of the virus was 2 9 .…”
Section: Peptides Aiv Vaccine and Micementioning
confidence: 99%
“…The H9N2 (A/chicken/Shandong/LY1/2017) strain was isolated and preserved in our laboratory [14], which was injected into a 9-day-old SPF chicken embryo allantoic cavity, and the allantoic fluid was collected and stored at −80 • C. SP2/0 cells were cultured in RPMI-1640 medium (Vicente Biotechnology Nanjing Co., Ltd., Nanjing, China) with 20% fetal bovine serum (FBS), 1% penicillin and 100 µg/mL streptomycin at 37 • C and 5% CO 2 .…”
Section: Viruses Cells and Plasmidsmentioning
confidence: 99%
“…To investigate the structural characteristics of NP proteins [14], the antigenicity was analyzed, as shown in Figure 1A. It was observed that the region between 71 and 243 AA in the NP protein possessed an apparent antigenic index, hydrophobicity and surface probability (Figure 1A, marked by the red box), which suggests that this region in the BP protein might have good antigenic characteristics and a B-cell determinant site.…”
Section: Cloning Expression and Purification Of Recombinant Np Proteinmentioning
confidence: 99%
See 1 more Smart Citation